Strategic Accountability and Economic Optimization of Samisade Village Fund Program in Bogor Regency - Fadhilah, Lubna; Nurdin, Nurliah (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines strategies to enhance accountability in the management of the One Billion One Village (Samisade) Program in Bogor Regency, Indonesia. The study is motivated by decentralization policies and the local government's efforts to accelerate rural development through Samisade (village infrastructure financial assistance). This research explores institutional and technical challenges that hinder the achievement of accountability in the implementation of the Samisade Program. This study adopts a descriptive qualitative approach through in-depth interviews and document analysis involving key stakeholders, such as village officials, the Department of Community Empowerment (DPMD), the Inspectorate, and the community. The findings indicate that low accountability is primarily caused by the uneven distribution of technological infrastructure among villages, limited availability of experts, and suboptimal human resource capacity in monitoring and evaluation. Furthermore, instances of misconduct and the involvement of village officials in legal cases were found, which further undermine the program’s credibility. To address these issues, the study recommends strengthening human resource capacity in supervision, ensuring equal distribution of supporting technological infrastructure, and providing technical assistance through expert assignments in the villages. From a policy perspective, this study emphasizes the importance of responsive and participatory multi-layered supervision. Theoretically, the study contributes to strengthening sustainable village governance by linking institutional readiness, program implementation effectiveness, and public accountability. It concludes that with appropriate interventions in capacity, infrastructure, and supervision, the Samisade Program can become a credible and impactful tool for rural development.